Dance for Health: the impact of creative dance sessions on older people in an acute hospital setting. Issue 1 (2nd January 2022) - Bungay, Hilary; Hughes, Suzanne; Jacobs, Clare; Zhang, Jufen
ABSTRACT: Background : This service evaluation examined the impact of Dance for Health, a programme of weekly group dance sessions for older patients, which took place on wards in an acute hospital setting. Methods : Qualitative and quantitative observations using the ArtsObs scale were undertaken of 64 dance sessions over a 12-week period involving seven different hospital wards encompassing 313 patient attendances. Results : Statistically significant improvements were observed in the mood of the majority of patients taking part. People engaged mentally and physically with the activity were distracted from their medical condition and from what was happening on the ward. Patients appeared relaxed and were willing to express themselves creatively. Conclusion : The Dance for Health programme had a positive impact on group participants, promoting movement and physical activity for older patients. It is a meaningful and enjoyable activity, which encourages social interaction and provides respite from the medical environment.